(untitled) (World Bulletin of Social Sciences, 2024)
In the article , formation of ecological culture in primary classes improving the quality of the educational process based on its content, forms and methods, theoretical, practical and educational importance, organization of ecological education in teaching natural science materials to students, the essence of lessons, as well as the infrastructure of its teaching are presented.